A hierarchical 3D-motion learning framework for animal spontaneous behavior mapping - Kang Huang (Nature Portfolio, 2021)
Animal behavior usually has a hierarchical structure and dynamics. Here, the authors propose a parallel and multi-layered framework to learn the hierarchical dynamics and generate an objective metric to map the behaviour into the feature space.